ADSORPSI ION MN(II) PADA ZEOLIT DARI ABU DASAR BATUBARA TERMODIFIKASI DITIZON - Riandy Putra; Khamidinal Khamidinal; Didik Krisdiyanto; Irwan Nugraha (Jurnal Kimia Terapan Indonesia, 2015)
Adsorption characteristic of Mn(II) on zeolite synthesized from bottom ash with alkaline hydrothermal conditions loaded with dithizone have been examined. The parameters studied includes effect of pH, contact time, initial concentrations and temperature of Mn(II) by batch experiments. The raw and modified samples were characterized by XRF, XRD, FT-IR and SAA. The results of XRD and FTIR showed that hydrothermal product consists of a mixture of zeolite (zeolite Y, zeolite Na-P and zeolite X) and sodalite crystals. Hydrothermal product showed specific IR absorption zeolite at wavenumber 300-1250 cm-1 and zeolite modified dithizone showed absorption -NH and –SH at wavenumber 1496,76 and 2461,17 cm-1. The results SAA showed that with addition dithizone lowering the specific surface area of zeolite from 160,262 m²/g  to 69,609 m²/g. Results of study show that adsorption of Mn(II) reaches its maximum values at pH 6 for zeolite and pH 8 for zeolite modified dithizone, respectively. The adsorption kinetics based on the pseudo-second-order rate equation with adsorption rate constants for zeolite synthesis -0,014 g/mg.min-1and for the zeolite modified dithizone 0,0204 g/mg.min-1. Based on the Langmuir equation, the maximum adsorption capacity (qmax) synthetic zeolite of 14,493 mg/g and zeolite modified dhitizone 15,873 mg/g. Termodynamic parameter indicated thatadsorption using two adsorbents takes place spontaneously at a lower temperature.Keywords: Bottom ash, zeolite, hydrothermal, dithizone, adsorption